Urban Soil: Assessing Ground Cover Impact on Surface Temperature and Thermal Comfort. Issue 1 (1st January 2016) - Brandani, Giada; Napoli, Marco; Massetti, Luciano; Petralli, Martina; Orlandini, Simone
Abstract : The urban population growth, together with the contemporary deindustrialization of metropolitan areas, has resulted in a large amount of available land with new possible uses. It is well known that urban green areas provide several benefits in the surrounding environment, such as the improvement of thermal comfort conditions for the population during summer heat waves. The purpose of this study is to provide useful information on thermal regimes of urban soils to urban planners to be used during an urban transformation to mitigate surface temperatures and improve human thermal comfort. Field measurements of solar radiation, surface temperature ( T s ), air temperature ( T air ), relative humidity, and wind speed were collected on four types of urban soils and pavements in the city of Florence during summer 2014. Analysis of days under calm, clear‐sky condition is reported. During daytime, sun‐to‐shadow differences for T air, apparent temperature index (ATI), and T s were significantly positive for all surfaces. Conversely, during nighttime, T air differences among all surfaces were significantly negative, whereas ATI showed significantly positive differences. Moreover, T s was significantly negative for grass and gravel. Relative to the shaded surfaces, T s was higher on white gravel and grass than gray sandstone and asphalt during nighttime, whereas gray sandstone was always the warmest surface during daytime. Conversely, no differences were found during nighttime for ATI and T air measured over surfaces that were exposed to sun during the day, whereas T s showed higher values on gravel than grass and asphalt during nighttime. An exposed surface warms less if its albedo is high, leading to a significant reduction of T s during daytime. These results underline the importance of considering the effects of surface characteristics on surface temperature and thermal comfort. This would be fundamental for addressing urban environment issues toward the heat island mitigation considering also the impact of urban renovation on microclimate. Core Ideas: In the daytime, average sun‐to‐shadow Tair, ATI, and Ts differences were positive for all surfaces. The nighttime Ts differences were only significantly negative for grass and gravel. The nighttime ATI differences were always significantly positive for all the surfaces. The nighttime Tair differences were often significantly negative for all surfaces.